The management of traumatic brain injury. Issue 9 (September 2017) - Roy, Holly; Richards, Peter
Abstract: Paediatric head injury is an important clinical problem. Essential management begins with initial resuscitation supporting the airway, breathing and circulatory systems with cervical spine stabilization. Neurological assessment should include evaluation of the Glasgow Coma Score and pupil reactivity. Further imaging, admission for observation and neurosurgical referral may be indicated. This article is aimed at the general paediatrician and emergency department physician. We discuss the epidemiology, pathophysiology and general principles of paediatric head injury management from the time of injury through to discharge from hospital.